(3Yde GdfaS GdCNdGbj (B/s - (3chaMj, bGSe eMeO eMehOs; (3ejQRG, Thbj eMeOs; (3NUGhfI, aDGO fLjHs ((3GdTGQbI (B[(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3ecJHI GdLGeYI ;s, 2012)
(3jJfGhd cJGH (B((3Yde GdfaS GdCNdGbj(B) (3hGdPj bGe HJCdjag O(B. (3bGSe eMeO chaMj HGdGTJQGc eY C(B. (3Thbj eMeO ejQRG hC(B. (3aDGO fLjH NUGhfI aj MhGdj (B(178) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3Yde faS GdCNdGb(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd HYfhGf Gdfeh GdCNdGbj, GdaUd GdKGfj HYfhGf GdGJLGgGJ GdfXQjI GdMOjKI ddCNdGb, GdaUd GdKGdK HYfhGf GdhGbYjI GdCNdGbjI, GdaUd GdQGHY HYfhGf GdfSHjI GdCNdGbjI, GdaUd GdNGeS HYfhGf GdJQHjI GdCNdGbjI, GdaUd GdSGOS HYfhGf ecGQe GdCNdGb(B.s
(3HHdjhLQGajI (B: (3UaMI (B175-176.s
Keywords: (3adSaI GdGNdGbs